Optimalisasi Kesehatan Ibu dan Anak melalui Edukasi Gizi Seimbang Berbasis Posyandu dalam Mendukung Kemandirian Ekonomi Keluarga - Kusumawardhani, Anindya; Maheswara, Raditya (Community : Jurnal Pengabdian Pada Masyarakat, 2025)
Maternal and child nutrition continue to be a serious issue in Indonesia, as seen from the high prevalence of stunting and limited knowledge of families about balanced diets. Such a situation has serious repercussions for children's growth and development, as well as for the overall economic productivity of the family. Posyandu, a community-based health program, offers a significant opportunity to deliver nutrition education and strengthen family economies through local food resources. This community service program applied an intervention method at posyandu explicitly targeted at pregnant women, mothers of children under five, and family representatives. Activities included nutrition education on balanced diets, demonstrations of local food processing, and training in small-scale enterprises producing healthy food products. The evaluation used both quantitative and qualitative methods, measuring knowledge, attitudes, and practices regarding child nutrition, as well as income improvements, and combining them with interviews and observations. These results have shown that maternal knowledge and practices improved significantly, along with better nutrition status among children under five years, and the development of local food-based micro-enterprises that have contributed to the family income. This program demonstrated the dual benefit of nutrition education married to family empowerment through posyandu: maternal and child health and economic autonomy for the family. Thus, it also becomes a sustainable model for defining community empowerment.